2022
DOI: 10.3390/children9091390
|View full text |Cite
|
Sign up to set email alerts
|

Facial Scanning Accuracy with Stereophotogrammetry and Smartphone Technology in Children: A Systematic Review

Abstract: The aim of the study was to systematically review and compare the accuracy of smartphone scanners versus stereophotogrammetry technology for facial digitization in children. A systematic literature search strategy of articles published from 1 January 2010 to 30 August 2022 was adopted through a combination of Mesh terms and free text words pooled through boolean operators on the following databases: PubMed, Scopus, Web of Science, Cochrane Library, LILACS, and OpenGrey. Twenty-three articles met the inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…In a recent study of D’Ettorre et al in 2022 [ 45 ], the surface-to-surface deviation analysis between Bellus3D and 3dMD(stereophotogrammetry) showed an overlap percentage of 80.01% ± 5.92% within the range of 1 mm discrepancy. A recent systematic review paper focusing on stereophotogrammetry and smartphone technology by Quinzi et al, 2022, concluded that “Stationary stereophotogrammetry devices showed a mean accuracy that ranged from 0.087 to 0.860 mm, portable stereophotogrammetry scanners from 0.150 to 0.849 mm, and smartphones from 0.460 to 1.400 mm.” [ 46 ]. The volumetric estimation errors are typically bigger in smartphone scanning than in photogrammetry [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of D’Ettorre et al in 2022 [ 45 ], the surface-to-surface deviation analysis between Bellus3D and 3dMD(stereophotogrammetry) showed an overlap percentage of 80.01% ± 5.92% within the range of 1 mm discrepancy. A recent systematic review paper focusing on stereophotogrammetry and smartphone technology by Quinzi et al, 2022, concluded that “Stationary stereophotogrammetry devices showed a mean accuracy that ranged from 0.087 to 0.860 mm, portable stereophotogrammetry scanners from 0.150 to 0.849 mm, and smartphones from 0.460 to 1.400 mm.” [ 46 ]. The volumetric estimation errors are typically bigger in smartphone scanning than in photogrammetry [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“… 19 Previous studies have proved its effectiveness in capturing the face, making it valuable for surgical planning and evaluation in maxillofacial surgery. 18 , 20 The Vectra M5 comes with the software VAM for SM analysis. 21 The software allows anthropometric measurements.…”
Section: Methodsmentioning
confidence: 99%
“…From this point of view, patients have to move to a dedicated motion analysis laboratory with a specific set of instruments that can detect and reproduce movements in three dimensions [28]. Currently, most analyses are performed in two dimensions [22], but some ongoing investigations aim to use simplified, portable, low-cost instruments such as smartphones to record threedimensional data [47]. This new technology may improve the quantitative analysis of patients with facial palsy.…”
Section: Limitationsmentioning
confidence: 99%